Transformasi Bawaslu dalam Mewujudkan Supremasi Pemilihan Umum - Kariem, Muhammad Quranul (Universitas Indo Global Mandiri, 2024)
This research aims to understand the transformation of the Election Supervisory Body (Bawaslu) in realizing the supremacy of elections. The research method used is a literature study with a qualitative descriptive approach. The results of the study indicate that the transformation of Bawaslu can be achieved by aligning the institution with judicial and law enforcement bodies. Additionally, for performance optimization, the use of algorithm-based information technology can be an alternative to achieve effective and efficient supervision. This condition can impact the establishment of election supremacy. The recommendation for this research is the formulation of a blueprint for the development of supervision methods and the mobilization of public support.